ANALYSIS OF THE EFFECT OF PHARMACEUTICAL SERVICE QUALITY ON CUSTOMER SATISFACTION AT A PHARMACY CHEMISTRY FARMA DENAI BUSINESS UNIT MEDAN - Tri Kurniawan; Endang Slistya Rini; Linda T. Maas (International Journal of Social Science, 2023)
This study aims to analyze the effect of pharmaceutical service quality on customer satisfaction at Kimia Farma Denai Pharmacy, Medan Business Unit, in 2020. This type of research is cross-sectional, in which the independent and dependent variables are studied simultaneously in the same period. As for what is examined in terms of service quality, namely reliability, assurance, responsiveness, physical evidence, and empathy. The population of this study was 1,980 visits with a total sample of 100 people. Data collection using chi-square test and multiple logistic regression test. The results showed that most of the respondents were 25-34 years old (37%), female (53%), had a bachelor's degree (39%), and worked as private employees (38%). The results of the analysis show that there is a relationship between reliability (p=0.003), assurance (p=0.031), physical evidence (p=0.044), empathy (p=0.021), and responsiveness (p=0.023) to customer satisfaction. The results of the analysis of the effect together show that reliability (p=0.006), guarantee (p=0.017), and physical form (p=0.033) have an effect on customer satisfaction, and the most influential variable is reliability (Exp B=4.732).